The diagnosis of fungal neglected tropical diseases (fungal NTDs) and the role of investigation and laboratory tests: An expert consensus report (2019)
The diagnosis of fungal Neglected Tropical Diseases (NTD) is primarily based on initial visual recognition of a suspected case followed by confirmatory laboratory testing, which is often limited to specialized facilities. Although molecular and serodiagnostic tools have advanced, a substantial gap remains between the desirable and the practical in endemic settings. To explore this issue further, we conducted a survey of subject matter experts on the optimal diagnostic methods sufficient to initiate treatment in well-equipped versus basic healthcare settings, as well as optimal sampling methods, for three fungal NTDs: mycetoma, chromoblastomycosis, and sporotrichosis. A survey of 23 centres found consensus on the key role of semi-invasive sampling methods such as biopsy diagnosis as compared with swabs or impression smears, and on the importance of histopathology, direct microscopy, and culture for mycetoma and chromoblastomycosis confirmation in well-equipped laboratories. In basic healthcare settings, direct microscopy combined with clinical signs were reported to be the most useful diagnostic indicators to prompt referral for treatment. The survey identified that the diagnosis of sporotrichosis is the most problematic with poor sensitivity across the most widely available laboratory tests except fungal culture, highlighting the need to improve mycological diagnostic capacity and to develop innovative diagnostic solutions. Fungal microscopy and culture are now recognized as WHO essential diagnostic tests and better training in their application will help improve the situation. For mycetoma and sporotrichosis, in particular, advances in identifying specific marker antigens or genomic sequences may pave the way for new laboratory-based or point-of-care tests, although this is a formidable task given the large number of different organisms that can cause fungal NTDs. © 2019 by the authors.